2021
DOI: 10.1002/cbdv.202000670
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterisation of Two Quercetin Glucosides with Potent Anti‐Reactive Oxygen Species (ROS) Activity and an Olean‐12‐en Triterpene Glucoside from the Fruit of Abelmoschus esculentus (L.) Moench

Abstract: Abelmoschus esculentus (Okra) is used in the traditional treatment of cancer, hyperlipidaemia and hyperglycaemia. We, therefore, investigated its composition and potential cytotoxic or antioxidant properties that might underlie its phytotherapeutic applications. Its methanolic fruit extract yielded compounds 1, 2 and 3, identified through NMR, UV and MS analyses as olean-12-en-3-O-β-D-glucopyranoside, isoquercitrin (quercetin glucoside) and 5,7,3',4'-tetrahydroxy-flavonol-3-O-[β-D-glucopyranosyl-(1!6)]-β-D-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Okra has been used in folkloric medicine in many parts of East Africa to treat kidney stones, diabetes, jaundice, gastritis, gastric ulcers, and other infections or ailments. Phytochemical analysis has shown that okra is a rich source of several potent bioactive components, such as catechin; epigallocatechin; isoquercitrin; rhamnogalacturonan; quercetin -β-d-glucopyranoside14; and oligomeric proanthocyanidins [193][194][195]. Most of these bioactive compounds have been shown to induce potent anticancer effects in several studies [24,193,196].…”
Section: Abelmoschus Esculentus (L) Moenchmentioning
confidence: 99%
See 2 more Smart Citations
“…Okra has been used in folkloric medicine in many parts of East Africa to treat kidney stones, diabetes, jaundice, gastritis, gastric ulcers, and other infections or ailments. Phytochemical analysis has shown that okra is a rich source of several potent bioactive components, such as catechin; epigallocatechin; isoquercitrin; rhamnogalacturonan; quercetin -β-d-glucopyranoside14; and oligomeric proanthocyanidins [193][194][195]. Most of these bioactive compounds have been shown to induce potent anticancer effects in several studies [24,193,196].…”
Section: Abelmoschus Esculentus (L) Moenchmentioning
confidence: 99%
“…Okra has been used in folkloric medicine in many parts of East Africa to treat kidney stones, diabetes, jaundice, gastritis, gastric ulcers, and other infections or ailments. Phytochemical analysis has shown that okra is a rich source of several potent bioactive components, such as catechin; epigallocatechin; isoquercitrin; rhamnogalacturonan; quercetin-3-O-sophoroside; quercetin-3-O-[glucosyl(1->6) glucoside]-7-O-rhamnoside; (3β,21β)-19,21-epoxylup-20(29)-en-3-yl acetate; (3β)-9,18-dihydroxyolean-12-en-3-yl acetate; polyphenolic groups of compounds like flavonoids; hydroxycinnamic derivatives; 5,7,3′,4′-tetrahydroxy flavonol-3-O-[β-d-rhamnopyranosyl-(1→2)]-β-d-glucopyranoside’ rutin; procyanidins B1 and B2; 5,7,3′,4′-tetrahydroxy-4″-O-methylflavonol-3-O-β-d-glucopyranoside; 5,7,3′,4′-tetrahydroxy flavonol-3-O-[β-d-glucopyranosyl-(1→6)]-β-d-glucopyranoside14; and oligomeric proanthocyanidins [ 193 , 194 , 195 ]. Most of these bioactive compounds have been shown to induce potent anticancer effects in several studies [ 24 , 193 , 196 ].…”
Section: Anticancer Effects and Cellular Targets Of Selected African ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles made using A. esculentus flower extracts showed antiproliferative, apoptotic and cytotoxic effects against A-549 and TERT-4 cancer cell lines. Quercetin diglucoside and isoquercitrin identified in A. esculentus were shown to be potently anti-ROS and thus could be used in cancer treatment ( Taiwo et al, 2021 ).…”
Section: Traditional African Medicinal Plants Used In the Management ...mentioning
confidence: 99%